PENERAPAN EVALUASI FORMATIF PADA PEMBELAJARAN TARI BEDANA DI SMK WIYATA KARYA NATAR - Fivita Ayu; Hasyimkan Hasyimkan; Fitri Daryanti (Jurnal Seni dan Pembelajaran, 2014)
This study aims to describe the process and results of the application of the formative evaluation of learning Bedana dance in SMK Wiyata Karya Natar. This research uses a qualitative descriptive method. Source of the data obtained in this study were 10 students who take extracurricular activities. Data collection techniques used were observation, interviews, documentation, and practices testing. Step of the implementation of formative evaluation is to formulate or reinforce the teaching objectives, set the